2021
DOI: 10.24925/turjaf.v9i6.1172-1179.4455
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Pretreatments on Hot air and Microwave-Hot Air Combined Drying of White Sweet Cherry

Abstract: Microwave (MW)-hot air (HA) combined drying was applied to white sweet cherries besides solely HA drying at 50, 60 and 70°C in the presence of citric acid, sucrose and freezing pretreatment in this study. Single power level of MW (90 W) was chosen, and drying behavior of all samples was modelled by using eleven thin layer equations. Two-term, rational and sigmoid models were the most suitable models for describing drying phenomena. Effective moisture diffusivities (Deff) ranged from 1.724×10-10 to 5.173×10-10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The highest value of the D eff was obtained in the MW‐CV dryer. Similar findings were reported by Çetin (2022c), Simsek and Süfer (2021), and Zhu et al (2022).…”
Section: Resultssupporting
confidence: 89%
“…The highest value of the D eff was obtained in the MW‐CV dryer. Similar findings were reported by Çetin (2022c), Simsek and Süfer (2021), and Zhu et al (2022).…”
Section: Resultssupporting
confidence: 89%
“…Their results showed that the minimum drying time (180 min) and the maximum D eff value (2.4 × 10 −9 m 2 /s) were obtained with freezing pretreatment, respectively. In another study, Simsek and Süfer ( 2021b ) examined the impacts of various pretreatments on combined hot air and microwave hot air drying of white SC. Their results confirm that the D eff value of white SC ranges from 1.7 × 10 −10 to 5.2 × 10 −10 m 2 /s in hot air drying and from 4.3 × 10 −10 to 1.8 × 10 −9 m 2 /s in microwave hot air drying.…”
Section: Resultsmentioning
confidence: 99%
“…The results of Simsek and Süfer ( 2021a ) confirmed that the freezing pretreatment improved the total phenolic content (4180 ± 0.86 μg GAE/g dry matter) and antioxidant capacity of dried white SC, as compared to control and other pretreatment methods. In another study, Simsek and Süfer ( 2021b ) examined the impacts of various pretreatments on combined hot air and hot air‐microwave drying of white SC. Their results confirmed that the total phenolic content of freezing pretreated and hot air dried at 50°C and hot air dried at 70°C control samples were 1481 and 6181 μg GAE/g, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…According to Siuci ńska et al [25], an ultrasound application during the osmotic pretreatment can result in a decrease in anthocyanin content and accelerate the loss of the antioxidant potential of stored convectively dried sour cherries. Simsek and Süfer [26] reported a reduced time for the microwave-hot air drying of white sweet cherries as a result of using 10% citric acid, 60% sucrose solutions, or a freezing pretreatment. In addition to osmotic dehydration, other pretreatment techniques can be used for sour cherries.…”
Section: Discussionmentioning
confidence: 99%